2013
DOI: 10.1016/j.bbr.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of shoaling in two zebrafish strains: A behavioral and neurochemical analysis

Abstract: Abnormal social behavior is a hallmark of several human neuropsychiatric and neurodevelopmental disorders for which appropriate treatment is lacking. The zebrafish has been proposed as a tool with which these disorders may be modeled and their mechanisms analyzed. A potential starting point of such analyses is the identification of genetic differences between distinct zebrafish strains. Here we compare AB and TU, two well established zebrafish strains, and characterize the developmental trajectories of their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 48 publications
5
68
2
Order By: Relevance
“…The zebrafish is a relatively new model in genetics and brain-behaviour research and differences between strains of zebrafish (Egan et al, 2009;Vignet et al, 2013;Wahlsten et al, 2006) as well as rearing conditions within and between laboratories (Mahabir et al, 2013;Parker et al, 2012;Pavlidis et al, 2013) may affect the outcome of experiments. Our data strongly suggest that at a behavioural and physiological level the UCS protocol is robust and reproducible in decreasing inhibitory learning and elevating whole-body cortisol content across strains of zebrafish, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish is a relatively new model in genetics and brain-behaviour research and differences between strains of zebrafish (Egan et al, 2009;Vignet et al, 2013;Wahlsten et al, 2006) as well as rearing conditions within and between laboratories (Mahabir et al, 2013;Parker et al, 2012;Pavlidis et al, 2013) may affect the outcome of experiments. Our data strongly suggest that at a behavioural and physiological level the UCS protocol is robust and reproducible in decreasing inhibitory learning and elevating whole-body cortisol content across strains of zebrafish, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While strain differences demonstrating the effects of genes on shoaling have been documented (Barba-Escobedo and Gould, 2012;Mahabir et al, 2013;Wright et al, 2003), no specific genes or quantitative trait loci associated with shoaling have been identified (Miller and Gerlai, 2007;2011b). Similarly, while changes in the levels of 11 Shams et al…”
Section: Social Behavior Of Zebrafishmentioning
confidence: 99%
“…Using HPLC (high-precision liquid chromatography) specifically developed for the detection of neurochemicals in zebrafish (Chatterjee and Gerlai, 2009), the amount of dopamine and DOPAC was analyzed from whole brain extracts of zebrafish. Zebrafish from age 15 to 102 dpf were tested, and the relative amount of dopamine and DOPAC was found to significantly Shams et al increase as the fish developed (Mahabir et al, 2013). Importantly, however, this agedependent maturation of the dopaminergic system was significantly blunted or arrested in fish exposed to alcohol during their embryonic development.…”
Section: Potential Mechanisms Underlying Embryonic Alcohol Exposure Imentioning
confidence: 99%
“…Furthermore, strong correlation between developmental changes in dopamine levels (relative to total brain protein) and the strength of shoaling during ontogenesis of zebrafish was also demonstrated (Buske & Gerlai, 2011). Last, Mahabir et al (2013) found alcohol administered during embryonic development to significantly impair both shoaling and the dopaminergic system, a result that brings up the last point to be discussed in this section: how one can utilize the knowledge one has gained about social behaviour of zebrafish in modelling and the analysis of a human CNS disorder.…”
Section: The Dopaminergic System and Shoalingmentioning
confidence: 90%